Private long-distance travel mode selection 1980 - Engström, Mats-G.; Sahlberg, Bengt (Nordic Institute for Studies in Urban and Regional Planning, 1983)
The principal purpose of the study was to identify and describe the factors which effect the choice of means of transportation for a longer private journey. Long journey here refers to trips of more than 100 km (one way). Private journey is defined as all travel with the exception of business, work, educational and military service trips. Information was collected by means of a postal questionnaire and home interviews. The primary purpose of the questionnaire was to select respondents for the interview who had undertaken at least one long journey during a three-month period, and who also could choose their means of travel. The interview contained questions about the purpose of the journey, number of nights away, means of transport used and company travelled with. The respondent had to indicate if other means of transport were considered and the importance of costs and travelling time.

Purpose:

Describe the factors which effect the choice of means of transportation for a longer privat journey

Forskningsprojektet 'Färdmedelsval vid långväga personresor' genomfördes på uppdrag av Transportforskningsdelegationen (TFD). Undersökningen genomfördes som en urvalsundersökning i två steg. Steg 1 utgjordes av en postal enkät, vars syfte var att urskilja individer som under en viss tidsperiod genomfört en längre privatresa och därmed antas ha gjort ett färdmedelsval. Steg 2 utgjordes av en personlig intervju med ett urval av dessa individer. Med långväga resor avses här resor på minst 10 mil enkel resa. Med privatresa menas alla resor, förutom tjänste-, arbetspendlings-, utbildnings- och värnpliktsresor. Även längre privatresor som ansluter till charterresor till utlandet medräknas. Undersökningen studerar endast resor inom de nordiska länderna. Intervjun innehöll frågor om resans ändamål, antal nätter man varit bortrest, typ av transportmedel samt vilket bolag man rest med. Respondenten fick även ange om man övervägt andra transportmedel och vilken betydelse kostnad och restid haft för val av transportmedel.

Syfte:

Klarlägga faktorer som påverkar valet av färdmedel vid långväga privata personresor
Färdmedelsval vid långväga privata personresor 1980
Keywords: public transport; kollektivtrafik; travel; resor; railway travel; tågresa; air travel; flygresor; road travel; vägresor; trains; tåg; cars; bilar; buses; bussar; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap